Proyecto de factibilidad para la implementación de una empresa de producción de baños de cajón portátiles y su comercialización en la provincia de Loja - Cortez Herrera, Cristian Junior (2015)
This study deals with the creation and implementation of the feasibility of implementing an enterprise production and marketing of portable baths drawer in the province of Loja. In the province of Loja no companies dedicated to the production and marketing of portable baths drawer. This is a great competitive advantage, being a pioneer in the implementation of an enterprise of production and marketing of portable baths drawer "THERMO - BATHROOM" CIA. Ltda.For the province of Loja, in order to provide families.A choice of alternative health from the comfort of your home. To develop the research project different methods and data collection techniques that helped me to prepare my study was used. Among the methods used is the deductive, inductive method, statistical method and who guided me to follow a logical process in my studio. Just as different techniques were also applied to gather information, such as direct observation, and surveys of a sample of 382 families in the province of Loja as potential customers. Regarding the study of market supply and demand was determined as well as the existing unmet demand and factors affecting product to offer such as Service, Price, Place, Promotion and Advertising. In the Technical Study performed the size that corresponds to the installed capacity was determined and used, and location of the project which details the macro and micro localization, attaching the sketch of the location of the company will be in the parish Valley in the neighborhood Sauces Northern urban area of Canton Loja whose physical space has all the basic facilities for normal operation, with respect to the project engineering component and technological tools for producing baths portable drawer exposed, distribution physics of the company, the production process in all its phases. Co. - On the organizational and administrative study, the legal organization established the company as a limited liability company, which will have two partners, whose name or business name is "BATH THERMO" is proposed. Ltda. In administrative and study the organizational structure arises through charts and manual functions. In the Financial Study shows that for the creation of the Company "THERMO - BATHROOM" CIA.Ltda. A $202.514,36 is required. The founding partners will contribute a total of $101.257,18 representing 50% of the investment and the difference with a credit forof $101.257,18 representing 50% of the investment. The Profit and Loss show a net profit of $40.269,45 in the first period and so on will increase in subsequent years. The evaluation of the project it became clear that the net present value is positive with a value of $ $291.898,99; the internal rate of return is 29,64% is greater than the opportunity cost of capital of 15 %; the benefit cost ratio indicates that for every dollar invested 0.32 cents performance is obtained; the investment will pay off in 4 years, 8 months and 1 day; and based on the sensitivity analysis a satisfactory result allowing 25,89% increase in costs and a decrease in revenue of 19.73%, respectively, the project is not sensitive to these changes is demonstrated. Co. - For implementing the conclusions, Company "BATH THERMO" is considered feasible. Ltda. Since identifying, the target market the interest of family’syokan’s in acquiring the bathroom drawer portable so it definitely is here reflected the bottom line of this research, which is logically observed, clear and concisely the results, based on a good study that precedes the project itself. Finally, conclusions and recommendations as the name suggests are suggestions that should be taken into account when making a decision for the implementation of the project are established